Landfill: an alternative to the disposal of solid waste - Caballero-Saldívar, Diana Elena (Universidad Autónoma de Tamaulipas, 2011)
Rapid population growth has increased the generation of municipal solid waste (MSW). In the past six decades, Mexico’s population grew from 30 million in 1950 (SEMARNAT-GTZ, 2004) to 112.337 million in the year 2010 (INEGI, 2010) and waste disposal increased from 3 million tons in the decade of the fifty (SEMARNAT-GTZ, 2004) to 40.1 million tons today (Sedesol, 2011). This means that each person generates about one kilogram of waste per day (SEMARNAT-GTZ, 2004). According Sedesol (2011), in 2010 the states with greatest waste disposal was the state of Mexico with 6.484 million tons and the Federal District with 4.847 million tons, while in Tamaulipas generated 1 159 000 tons of waste. It is important to know what the final destination of such waste is, for example, in Mexico during 2010 alone deposited in landfills 70% of the MSW produced. Landfills are a technical and economic alternative for a proper management of municipal solid waste, thus decreasing the damage to the environment and health of the population (Villafuerte et al., 2004). The aim of this paper is to show the importance of the landfill as an alternative for disposal of solid waste generated by the population.